A simplified beam model for the numerical analysis of masonry arch bridges –A case study of the Veresk railway bridge. (November 2022) - Rahimi, Arash; Aval, S. Bahram Beheshti; Noori, Mohammad; Sarhosis, Vasilis; Wu, Zhishen; Nikkhoo, Ali; Altabey, Wael A.
Abstract: This paper presents the development of a simplified analytical model, able to substitute high fidelity-three-dimensional (3D) finite element (FE) models, for the analysis of complex mechanical and civil structures such as masonry arch bridges. The non-uniform mass and stiffness distribution along the length of masonry arch bridges presents significant challenges when used for the development of beam models. Such models can be coupled with structural health monitoring schemes for the development of quick online decision-making tools and the optimal structure operation and management. As a case study, the behavior of the Veresk railway masonry arch bridge located in north Iran was investigated. Initially, the dynamic behavior of the bridge has been structurally assessed using a complex 3D FE model under operational load conditions. The 3D FE model was calibrated against field data from sensors placed in the bridge. Later, a simplified model using the dynamic parameters equivalent to the bridge has been developed and subjected to operational moving loads, masses and oscillators. The results of maximum displacement spectra were derived under the passage of different in mass and speed trains using an undamped/damped beam model. The analytical results of the beam model present good accuracy when compared with those from the three-dimensional finite element model.